Incidence of healthcare-associated Clostridioides difficile infections and association with ward-level antibiotic consumption in a German university hospital: an ecological study. (16th May 2019) - Kipnis, Marina; Schwab, Frank; Kramer, Tobias S; Stegemann, Miriam S; Isner, Caroline; Pilarski, Georg; Märtin, Nayana; Bui, Minh Trang; Boldt, Anne-C; Behnke, Michael; Denkel, Luisa A; Wiese-Posselt, Miriam; et al.
Abstract: Objectives: Clostridioides difficile infection (CDI) is one of the most important healthcare-associated infections. We aimed to describe the incidence density of healthcare-associated CDI (HA-CDI) in Germany's largest hospital and to identify associations with ward-level antimicrobial consumption. Methods: We used surveillance data on CDI and antimicrobial consumption from 2014 to 2017 and analysed a potential association by means of multivariable regression analysis. Results: We included 77 wards with 404998 admitted patients and 1850862 patient-days. Six hundred and seventy-one HA-CDI cases were identified, resulting in a pooled mean incidence density of 0.36/1000 patient-days (IQR = 0.34–0.39). HA-CDI incidence density on ICU and haematological–oncological wards was about three times higher than on surgical wards [incidence rate ratio (IRR) = 3.00 (95% CI = 1.96–4.60) and IRR = 2.78 (95% CI = 1.88–4.11), respectively]. Ward-level consumption of third-generation cephalosporins was the sole antimicrobial risk factor for HA-CDI. With each DDD/100 patient-days administered, a ward's HA-CDI incidence density increased by 2% [IRR = 1.02 (95% CI = 1.01–1.04)]. Other risk factors were contemporaneous community-associated CDI cases [IRR = 1.32 (95% CI = 1.07–1.63)] and CDI cases in the previous month [IRR = 1.27 (95% CI = 1.07–1.51)]. Furthermore, we found a significant decrease in HA-CDI in 2017 compared with 2014 [IRR = 0.68 (95% CI = 0.54–0.86)]. Conclusions: We confirmed that ward-level antimicrobial use influences HA-CDI and specifically identified third-generation cephalosporin consumption as a risk factor.